2013
DOI: 10.1371/journal.pone.0066997
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Dynamic and Static Facial Expressions of Happiness and Disgust Investigated by ERPs and fMRI Constrained Source Analysis

Abstract: A recent functional magnetic resonance imaging (fMRI) study by our group demonstrated that dynamic emotional faces are more accurately recognized and evoked more widespread patterns of hemodynamic brain responses than static emotional faces. Based on this experimental design, the present study aimed at investigating the spatio-temporal processing of static and dynamic emotional facial expressions in 19 healthy women by means of multi-channel electroencephalography (EEG), event-related potentials (ERP) and fMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 66 publications
(131 reference statements)
7
33
1
Order By: Relevance
“…ERP differences were not limited to N1 but also occurred for P2. Persistent differences in the LPC range are visible in the FDR-corrected t -maps and this is consistent with enhancement of the late positive potentials (LPC) for dynamic emotional faces [33]. Frontal P2 and was greatest for neutral-angry transitions (Fig 2).…”
Section: Discussionsupporting
confidence: 65%
“…ERP differences were not limited to N1 but also occurred for P2. Persistent differences in the LPC range are visible in the FDR-corrected t -maps and this is consistent with enhancement of the late positive potentials (LPC) for dynamic emotional faces [33]. Frontal P2 and was greatest for neutral-angry transitions (Fig 2).…”
Section: Discussionsupporting
confidence: 65%
“…It is well-established that facial motion and dynamic facial expressions enhance signal strength in face recognition and emotion processing areas such as the right superior temporal sulcus, the bilateral fusiform face area, and the inferior occipital gyrus (Schultz & Pilz, 2009; Trautmann et al, 2009; and Recio et al, 2011). Further, dynamic faces enhance differentiation of emotional valences (Trautmann-Lengsfeld et al, 2013), and engage motion sensitive systems (Furl et al, 2010; Sato et al, 2004). However, these stimulus complexities and systems are associated with faces and context processing, whereas, the focus of this study was on eyes-only (which was confirmed by the eye-tracking and gaze locations).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic face stimuli, compared to static pictures, have also been associated with enhanced differentiation of emotional valences (Trautmann-Lengsfeld et al, 2013), and these systems were found to be sensitive to the rate of facial movement (Schultz et al, 2013). Moving trajectories of facial expressions morphed from neutral to either a positive or negative valence and recorded by magnetoencephalography (MEG) revealed similar findings with the added observation that pre-motor activity was concomitant with activity in the temporal visual areas, suggesting that motion sensitive mechanisms associated with dynamic facial expressions may also predict facial expression trajectories (Furl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Ecological validity of both animal and human studies on the neural organisation of emotion processing is mostly limited by several factors, such as a lack of realistic emotion-inducing stimulation [6,8,21,23], missing or inappropriate control conditions for the differentiation between emotion, arousal and/or task complexity-effects [6,8], or sample characteristics (e.g., emotion processing in patients with particular brain lesions that might be assigned to both specific lesion location or coping with behavioural disorders or even by the interaction of both). The detailed analysis of individual differences appears to be a crucial aspect that is mostly neglected, although there is evidence that there is more individuality than overlap in the processing of complex emotional content [18].…”
mentioning
confidence: 99%
“…This idea particularly considers higher principles of emotion processing, hosted in different affect and emotional effector systems that are highly cross-linked and operate together at different complexity levels. However, we additionally need, beside contemporary theoretical innovations [3,6,9,13,14], new and advanced analytical approaches to better catch spatio-temporal and individual characteristics of neural emotion-processing [1,7,16,18,22], and new experimental designs more validly inducing emotional brain responses [e.g., 8,21] appear to be necessary for a comprehensive testing of the here proposed theory of human emotion and to further explore the complexity of interactions and processing principles of the proposed sub-systems.…”
mentioning
confidence: 99%